Qualidade da atenção aos idosos: risco de lesão por pressão como condição marcadora - Viviani Camboin Meireles; Vanessa Denardi Antoniassi Baldissera (Universidade Federal do Ceará, 2019)
Objective to analyze the quality of care provided in primary health care to frail elderly individuals at risk of pressure injury.Methods multiple case study. Sixteen elderly and their family caregivers and ten health professionals participated in the study.Results among nonconformities were the non-realization of screening of the degree of frailty and multidimensional evaluation of the elderly; absence of pressure injury risk assessment; scarcity of material and human resources; lack of support for family caregivers; delay in meeting the needs of equipment for mobilization; lack of knowledge on the part of professionals and caregivers.Conclusion the study led to the conclusion that the marker is a tool that evaluates the course of care and, in the case of frail elderly people with risk for pressure injury, and fragilities range from professional knowledge to systematic practices that include the care network.